The Relationship between Servant Leadership & Organizational Learning and Nurses' Work Engagement - Peyman Akharbin; Adel Zahed Babolan; Abbas Naghizadeh Baghi (Golestan University of Medical Sciences, 2014)
Background and Objective: One of the most important motivating factors of nurses is the improvement of their work engagement. Since the job engagement can be affected by various factors including the leadership style of nurse managers and organizational learning, this study aimed to investigate the relationship between servant leadership and organizational learning and work engagement of nurses in Ardabil University of Medical Sciences. Material and Methods: This cross-sectional study was conducted on 273 of 914 nurses working in the hospitals affiliated to Ardabil University of Medical Sciences. The sample size (N= 273) determined via Krejcie and Morgan table were asked to fill out the three questionnaires of Servant leadership style (by Gholipour et al), organizational learning (by Chiva et al) and job engagement (by Salanova and Schaufeli). The data was analyzed by SPSS-21, using descriptive statistics (data frequency tables, mean, and standard deviation) and inferential statistics (stepwise multiple regression method and Pearson correlation). Results: The results showd that there was a positive and significant relationship between servant leadership, organizational learning, and job engagement (p≤0.01). Furthermore, servant leadership and organizational learning can predict job engagement. Conclusion: The improvement of organizational learning and servant leadership can enhance the nurses' job engagement.